Al-Biruni on transits : a study of an Arabic treatise entitled Tamhid al-mustaqarr li-tahqiq ma’na al-mamarr - el-Biruni, Ebü’r-Reyhan Muhammed bin Ahmed, 973-1061 (Frankfurt am Main)
ix, 201, [27] s.